PERBEDAAN FAKTOR PENGARUH MINAT KULIAH DI STIE SURAKARTA (Studi Kasus pada SMA Al-Azhar Syifa Budi Solo) - Ira Widyowati; Atik Lusia (J-MIND (Jurnal Manajemen Indonesia), 2023)
This study aims to obtain information about the differences in influence between brand awareness, student perceptions, and social media marketing on students' interest in enrolling in the Surakarta Economics College before and after the socialization of STIES at Al-Azhar Syifa Budi Solo High School. Class XII students became the population used in this study and 54 students were the number of samples used. Saturated sampling or census is the choice of sampling technique by researchers in this study. The data analysis method used the Paired T-Test. The results of the Paired T-Test analysis show that brand awareness, student perceptions, and social media marketing have a positive and significant difference in influence on students' interest in studying at SMA Al-Azhar Syifa Budi Solo to STIES before and after socialization.